Recalibrating teacher training in African higher education institutions A focus on 21st-century pedagogical challenges - Matashu, Martha (AOSIS, 2022)
This book critically examines the role of governments in promoting parity during and in post-pandemic education. This comes from the realisation that the pandemic has deepened the crisis by depleting the meagre resources that African countries might have devoted to 'normative educational practices' where those on the margins would have been pushed further behind while the privileged would have been further initiated into the cultural and capital flows of private schools and historically research-intensive institutions of higher learning. This has far-reaching implications for the education of underprivileged citizens, and education, particularly modes and modalities of delivery, has to be reimagined to subvert the challenges wrought by the pandemic. This book significantly bridges the gap between the pre-and post-COVID-19 pandemic pedagogical practices and the erstwhile modalities that have been resilient over time. The book focuses on ways to stave off pedagogical challenges that face countries as the global pandemic makes its mark.